An 18-bit 2-2 MASH delta-sigma modulator for isolated amplifier. (June 2023) - Yu, Wenxin; He, Lenian; Xi, Jianxiong
Abstract: This paper presents an 18-bit 2-2 MASH delta-sigma modulator (DSM) for the isolated amplifier. Combining the cascade of integrators with feedforward (CIFF) structure and the cascade of integrators with feedback (CIFB) structure, the DSM effectively results in reduced harmonic distortion. Gain boost and slew rate (SR) boost techniques are used to enhance the performance of the first stage integrator. To reduce low-frequency noise, the chopper technique is adopted as well. The DSM was fabricated in a 0.18 μm CMOS process with an active area of 0.90 mm 2, dissipating 29.70 mW under a 3.3 V supply with the Schreier figure-of-merit (FoMs) 170.00 dB. The 108.71 dB signal-to-noise and distortion ratio (SNDR) and 17.77 bits the effective number of bits (ENOB) are achieved by simulation in a 20 kHz bandwidth.